FAM117B promotes gastric cancer growth and drug resistance by targeting the KEAP1/NRF2 signaling pathway - Yunjiang Zhou; Yaxin Chen; Yongwei Shi; Leyin Wu; Yingying Tan; Tao Li; Yigang Chen; Jiazeng Xia; Rong Hu (The Journal of Clinical Investigation, 2023)
Gastric cancer often shows malignant growth and insensitivity to chemotherapeutic drugs due to the regulation of complex molecular mechanisms, which results in poor prognosis for patients. However, the relevant molecular mechanisms remain unclear. In this study, we reported that family with sequence similarity 117, member B (FAM117B), promoted the growth of gastric cancer cells and reduced the sensitivity of cells to chemotherapeutic drugs. Mechanistically, FAM117B competed with nuclear factor E2–related factor 2 (NRF2) for Kelch-like ECH-associated protein 1 (KEAP1) binding, reduced the ubiquitination degradation of NRF2, and activated the KEAP1/NRF2 signaling pathway. Moreover, FAM117B-induced growth and chemoresistance of gastric cancer cells were NRF2 dependent. We found that FAM117B and NRF2 protein levels were highly expressed in tumor tissues of patients with gastric cancer and their co-overexpression represented an independent factor for poor prognosis. Collectively, our findings reveal that FAM117B is involved in promoting gastric cancer growth and drug resistance, and it could be exploited as a cancer therapeutic target.